Guía interpretativa de los motivos simbólicos de Homo faber - Cortés, Helena (Revista de Filología Alemana, 2002)
This article is an attempt to present an exhaustive and interpretative guide to the many symbolic aspects in Max Frisch’s HOMO FABER. Although some of these symbols are very evident, others are not, and demand a very good knowledge of the Greek culture and a solid interpretation to reach the deep level of the novel. With this work we hope that the common cultivated reader might achieve an integral reading of the novel on its many levels. First we analyze the symbolic use of TIME and its many mergings with the meaning and the formal structure of the novel: Faber’s travels, the analepses and prolepses, their use and meaning. Afterwards we proceed to a counting and detailed analysis of the many symbolic aspects of the novel in connection with the Greek world —aspects that allow and confirm the possible interpretation of the novel as a modern Greek tragedy about destiny— beginning with the masculine mythological figures hiding under the main protagonist Faber (Ulisses, Agamenon, Edipus, etc.), and ending with topics such as blindness, Greek art, the placenames, etc. We also analyze the symbolic topics in relation with nature (the moon eclipse, etc.), the physical and psychological sensations (like cold and heat, trembling, etc.) and we conclude with an analysis of the symbolic value of colours (red and black) in the novel.